Singer’s Midgets in Karlín’s Theatre Varieté: Strategies of Representing Physical Difference in 1920s Prague - Herza, Filip (Dějiny – teorie – kritika, 2011)
Prague show of Singer’s Midgets is presented here as an extraordinarily impressive depiction of bourgeois values and contemporary notions of physical ab/normality. This text analyses representation strategies, key discourses and rhetorical figures used in the Singer’s Midgets performance to describe the relation between extraordinary bodies and their audience, but also to better understand the complex process of construction of the ab/normal identities in the late 1920s in Czechoslovak republic. The study places the exhibition of human ‘curiosities’ into the context or Euro-American tradition of freak shows, while taking into account the specific features of the Czech environment. The use of satirical and comical rhetoric in the performances of Singer’s group seems to be specific to Czech milieu. It facilitated a criticism of the ‘small Czech life’ as well as constituted a link between the ‘midgets’ and a republican discourse and thus buttressed in the 1920s the hegemonial bourgeois identity.